2005
DOI: 10.1055/s-2005-871248
|View full text |Cite
|
Sign up to set email alerts
|

Crocetin Prevents Dexamethasone-Induced Insulin Resistance in Rats

Abstract: The main objective of the study was to examine whether crocetin, a natural product from Gardenia jaminoides Ellis, has beneficial effects on the state of insulin resistance induced by dexamethasone in a rat model. Measured using the oral glucose tolerance tests (OGTT), male Wistar rats treated with subcutaneous dexamethasone (0.08 mg/kg/d) for 6 weeks exhibited reduced insulin sensitivity at weeks 2 and 4 and impaired glucose tolerance at week 4. In the dexamethasone-treated group, serum insulin, free fatty ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 28 publications
0
39
0
Order By: Relevance
“…Recent studies have also demonstrated the potential of crocetin to reduce insulin resistance in rats (Xi, Qian, Shen, Wen, & Zhang, 2005;Xi et al, 2007). In a 2005 study, rats were administered dexamethasone (a glucocorticoid that contributes to insulin resistance) and dexamethasone+ crocetin for a six-week period.…”
Section: Insulin Resistancementioning
confidence: 98%
“…Recent studies have also demonstrated the potential of crocetin to reduce insulin resistance in rats (Xi, Qian, Shen, Wen, & Zhang, 2005;Xi et al, 2007). In a 2005 study, rats were administered dexamethasone (a glucocorticoid that contributes to insulin resistance) and dexamethasone+ crocetin for a six-week period.…”
Section: Insulin Resistancementioning
confidence: 98%
“…1, >98%, HPLC), a carotenoid compound, was isolated from Gardenia jasminoids Ellis by our laboratory (Xi et al, 2005). Our recent study showed that crocetin inhibits angiotensin II (Ang II)-induced proliferation of VSMCs (Zhou et al, 2006).…”
Section: Introductionmentioning
confidence: 98%
“…Further reasons to focus on CCT are that this compound can be obtained from various sources other than saffron, such as Gardenia jasminoides Ellis, and it has favorable cardiovascular effects, such as a decrease in oxidative stress [12,13,14] and inhibitory action on the development of insulin resistance [15,16]. Other related studies have determined that CCT can ameliorate the effects of atherosclerosis and related diseases [12,15,16,17,18,19,20]. …”
Section: Introductionmentioning
confidence: 99%